KAJIAN INTERTEKSTUAL NOVEL CINTA BERTABUR DI LANGIT MEKKAH KARYA ROIDAH DAN NOVEL ASMARA DI ATAS HARAM KARYA ZULKIFLI L. MUCHDI DENGAN PENDEKATAN SOSIOLOGI - Nurul Azizah, Ririn (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Literary works in this era of progress have been very developed. The creation of literary works is usually influenced by the literary works that preceded it. The literary work that precedes is used as an example or role model for later literary works. Two or more literary works with the same theme have similarities and differences. Similarities and differences in several literary works can be analyzed using the principle of intertextuality. This principle is intended to examine texts that are considered to have a certain relationship with other texts so that it is possible for a work to become a hypogram for subsequent literary works. In this study the author chose the title